The Role of Tax Evasion in The Risk of Corporate Bankruptcy: A Field Study in The Business Environment in The Kurdistan Region of Iraq - Khowanas Saeed Qader; Sanarya Adnan Anwer; Hawkar Anwar Hamad; Hamin Khasrow Ibrahim; Bayar Gardi; Pshdar Abdalla Hamza; Rizhin Nuree Othman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Tax avoidance causes a high level of information opacity among businesses, lowering the accuracy of accounting data. To control audit risks that may occur from tax avoidance, auditors must undertake additional auditing procedures, resulting in increased audit fees. The current study applied quantitative research method through using academic questionnaire to examine the relationship between corporate tax avoidance and firms’ bankruptcy risks. The population of the current study is firms in Kurdistan region of Iraq and particularly in Erbil. The study distrusted 120 questionnaires however only 109 questionnaires were obtained, all questionnaires distributed by using simple random method. Companies should be able to observe the effects/consequences of tax evasion on the firm’s risk and future tax rate volatility in order to retain investors interested in making safe investments in the company. The findings demonstrated that all four research hypotheses are supported, means that controlling corporate tax avoidance by applying (tax management, tax planning, tax aggressiveness, and tax evasion) will have positive and significant influence on firms’ risk bankruptcy.